2017
DOI: 10.2298/yjor140115013k
|View full text |Cite
|
Sign up to set email alerts
|

A model of the supplier involvement in the product innovation

Abstract: In this paper we examine the product innovation in a supply chain by a supplier and derive a model for a supplier's product innovation policy. The product innovation of a supplier can contribute to the long-term competitiveness for the supply chain, and as it is for many supply chains a major factor, it should be considered in the development of strategies for a supplier. Here, we evaluate the effectiveness of supplier product innovation as a strategic tool to enhance the competitiveness and viability of suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…The positive relationship of the barrier to lack of information on technology with the innovation of processes found in Ecuadorian companies concurs with Stankovska et al (2016), they found, in UK SMEs, that the lack of information on technology affects the company's innovative performance. Technology, especially that used in production plants and the technology that comes from suppliers, is an important source of information (Kumar et al 2017). When this barrier exists, companies find their innovative potential restricted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive relationship of the barrier to lack of information on technology with the innovation of processes found in Ecuadorian companies concurs with Stankovska et al (2016), they found, in UK SMEs, that the lack of information on technology affects the company's innovative performance. Technology, especially that used in production plants and the technology that comes from suppliers, is an important source of information (Kumar et al 2017). When this barrier exists, companies find their innovative potential restricted.…”
Section: Discussionmentioning
confidence: 99%
“…Customers provide information about their needs (Pejić Bach et al 2015) and their experiences with the products (Gu et al 2016). Cooperation with external market actors such as customers, suppliers, competitors, and consultants allows for an increasing flow of external knowledge to the company (Chang and Taylor 2016;Estrada et al 2016;Kumar et al 2017). Cooperation for innovation is a strategic action between organizations that seek reciprocal incentives and benefits (Arranz et al 2019).…”
Section: Knowledge Factor Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Los clientes son importantes porque brindan información sobre sus necesidades y porque brindan opiniones sobre los productos de la empresa, cuando la innovación se diseña considerando la opinión de los clientes, tiene grandes posibilidades de éxito en el mercado [5,6]. Considerando el conocimiento que aporta los clientes para la innovación orientada a la sostenibilidad en la empresa, se plantea la siguiente hipótesis: H3 = Los clientes se relaciona positivamente con la innovación de productos y servicios en empresas orientadas a la sostenibilidad Los proveedores son importantes porque aportan tecnologías especialmente para la fabricación del producto y porque realizan su propia innovación en las partes del producto que la empresa innova [43,44]. Considerando el conocimiento que aporta los proveedores para la innovación orientada a la sostenibilidad en la empresa, se plantea la siguiente hipótesis: H4 = Los proveedores se relaciona positivamente con la innovación de productos y servicios en empresas orientadas a la sostenibilidad Los competidores son importantes porque brindan una base de conocimiento para el desarrollo de la innovación o porque pueden desarrollar la innovación junto con la empresa y al mismo tiempo pueden compartir el conocimiento de sus propios proveedores con la empresa [45].…”
Section: Do Not Removeunclassified
“…El objetivo de esta investigación fue determinar la relación entre las fuentes de conocimiento (I+D interna y externa, clientes, proveedores y competidores) y la innovación (de productos y procesos) orientada a la sostenibilidad, ya que estas empresas se enfocan en la reducción de materiales y energía, mejorar la salud y seguridad en el trabajo y reducir el impacto ambiental [1] y para lograr estos objetivos deben disponer de obtener conocimientos, modificar procesos y colaboración con otros actores del mercado [4,5] y es de interés conocer como las empresas innovadoras de países en desarrollo obtienen el conocimiento para lograr estos objetivos, especialmente debido a que es escasa la evidencia en países en desarrollo Los resultados en la innovación de productos muestran algunas peculiaridades de las empresas ecuatorianas orientadas a la innovación sostenible. En primer lugar, la I+D interna es muy importante para estas empresas junto al conocimiento de los clientes que proporcionan conocimiento sobre sus necesidades [5,6], esto es una característica particular de este tipo de empresa ya que en los países en desarrollo algunas empresas alcanzan la innovación tradicional sólo con adquisición de equipos y en general prefieren adquirir tecnología que desarrollarla en I+D interna [2] o desarrollan innovación a través del conocimiento de proveedores [43,44]. En los resultados se muestra que la innovación de productos orientada a la sostenibilidad, la relación con los proveedores es negativa en las empresas ecuatorianas, lo que muestra que esta fuente de conocimiento no es importante para la innovación de productos.…”
Section: Tabla I Composición De Variablesunclassified